Understanding comics-based research : a practical guide for social scientists - Moretti, Veronica (Emerald Publishing Limited, 2023)
Understanding Comics-Based Research focuses on the contribution that comics can make to social research as part of a "Graphic social science" construct. Comics and graphic novels offer a juxtaposition of text and images bringing community-based participatory research multiple opportunities for communication. In this exploratory volume, Veronica Moretti illustrates how the graphic medium can help elicit participant's narratives and how it supports new guiding principles in research, along with what barriers researchers may encounter using comics, and to what extent comics can be incorporated within traditional social research techniques.
Keywords: Social sciences -- Research -- Methodology.; Comic books, strips, etc. -- History and criticism.; Social Science -- Research.; Social research & statistics.; elektronické knihy; electronic books